Prevalence of knowledge, attitudes, and practices regarding antimicrobial resistance in Africa: a systematic review and meta-analysis - Atalay, Yibeltal Assefa; Abebe Gelaw, Kelemu (Frontiers in Microbiology, 2024)
Background: One of the main threats to public health today is antibiotic resistance. This resistance leads to the persistence of infections in the body. It poses an increased risk of transmission to humans. .Objectives: This study aimed to ascertain the overall prevalence of Knowledge, Attitudes, and practices regarding antimicrobial resistance in Africa.A systematic review and meta-analysis of published and unpublished studies was conducted in Africa according to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. Searches were conducted using appropriate search terms in PubMed, Web of Science, Science Direct, Google Scholar, African Journals Online, and the Cochrane Library. Data were extracted using Microsoft Excel, and STATA version 14 was used for analysis. A p-value of 0.05 was regarded to indicating potential publication bias. Using I2 statistics, the heterogeneity of the studies was evaluated. Using forest plots, the random effect model was used to present the pooled prevalence with a 95% confidence interval (CI) of meta-analysis.Results: This review included 39 studies, with 18,769 study participants. Among these thirty-nine studies, 38 were on knowledge assessment, 28 on attitude assessment, and 25 on good practice assessment towards antimicrobial resistance. The overall pooled prevalence level of knowledge regarding antimicrobial resistance in Africa was 55.33% (95% CI: 47.48, 63.18). The overall pooled prevalence of positive attitudes toward antimicrobial resistance in Africa was 46.93 % (95% CI: 35.10, 58.76), and the overall pooled prevalence of good practice of antimicrobial resistance in Africa was 51.05 % (95% CI: 45.24, 56.87). .In Africa, the pooled prevalence of knowledge, attitudes, and practices regarding antimicrobial drug resistance among different groups, including the general population, patients, tertiary school students, healthcare workers, and animal owners, was found to be low. The meta-analysis conducted in this review revealed significant gaps in knowledge, attitudes, and practices regarding antimicrobial drug resistance among different groups, including the general population, patients, students, healthcare workers, and animal owners. Therefore, it is imperative to enhance the education and training programs regarding antibiotic resistance for various groups, including the general public, patients, students, healthcare workers,.